2018
DOI: 10.30773/pi.2018.07.29.2
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant Tendency of Noncurrent Emotional Experiences in Individuals at Ultra-High Risk for Psychosis

Abstract: ObjectiveThis study aimed to investigate whether aberrant tendency of noncurrent emotion was present in individuals at ultra-high risk (UHR) for psychosis and to explore its associations with various clinical profiles. MethodsFifty-seven individuals at UHR and 49 normal controls were enrolled. The tendency of experiencing noncurrent emotion was assessed using various noncurrent emotional self-reported formats, including trait [Neuroticism and Extraversion of the Eysenck Personality Questionnaire], hypothetical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 46 publications
1
7
0
Order By: Relevance
“…We used the Korean version of the Magical Ideation Scale and Social Anhedonia Scale, which is widely used in Korean psychiatric research. 35,48,49 In the present study, the internal consistency (Cronbach's alpha) of the Magical Ideation Scale was 0.76, and that of the Revised Social Anhedonia Scale was 0.93.…”
Section: Assessment Of Self-reported Schizotypysupporting
confidence: 47%
See 1 more Smart Citation
“…We used the Korean version of the Magical Ideation Scale and Social Anhedonia Scale, which is widely used in Korean psychiatric research. 35,48,49 In the present study, the internal consistency (Cronbach's alpha) of the Magical Ideation Scale was 0.76, and that of the Revised Social Anhedonia Scale was 0.93.…”
Section: Assessment Of Self-reported Schizotypysupporting
confidence: 47%
“…The Magical Ideation Scale represents the positive aspect of schizotypy, whereas the Revised Social Anhedonia scale represents the negative aspect of schizotypy. We used the Korean version of the Magical Ideation Scale and Social Anhedonia Scale, which is widely used in Korean psychiatric research [ 35 , 48 , 49 ]. In the present study, the internal consistency (Cronbach’s alpha) of the Magical Ideation Scale was 0.76, and that of the Revised Social Anhedonia Scale was 0.93.…”
Section: Methodsmentioning
confidence: 99%
“…28,[33][34][35][36] To our knowledge, only one study has evaluated trait positive and negative affect in individuals at CHR for psychosis. Seo and colleagues 37 found that individuals at CHR reported lower levels of trait positive and higher levels of trait negative affect. Moreover, only negative symptoms predicted individual differences in both higher negative and lower positive trait affect.…”
Section: Discussionmentioning
confidence: 99%
“…These findings add important specificity for studies showing links between emotions and negative symptoms. 5,37 The breadth of interconnectedness between trait emotion, symptoms and functioning highlights not only the generalised pathology of emotion abnormalities in the population at CHR for psychosis, but also the importance of making emotions the target of interventions for improving functional outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Studies included in the meta-analysis portion of this review are described in Table 1, most studies were conducted in North America (n=9), [38][39][40][41][42][43][44][45][46] followed by Asia (n=5), [47][48][49][50][51] Europe (n=4), 33,34,52,53 and Australia (n=3). [54][55][56] There were fourteen cross-sectional studies and seven longitudinal studies.…”
Section: Meta-analysis Study and Participant Characteristicsmentioning
confidence: 99%